2023
DOI: 10.12968/ukve.2023.7.5.196
|View full text |Cite
|
Sign up to set email alerts
|

Equestrianism's social license to operate: assumptions, reality and the future

Jane M. Williams

Abstract: Horse sports and equestrian activities are high risk to the horses and people undertaking them. Societal views on using animals for human entertainment are changing and there is increased debate on how animal welfare is safeguarded. Traditional management systems that reduce opportunities for expression of normal behaviour and high levels of disease and injury in horses interacting with humans have increased public scrutiny on the use of horses by humans, resulting in equestrianism's social license to operate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A good starting point to promote sporthorse health and welfare and establish an effective SLO for horse sports would be to develop an evidence-based infrastructure to inform the management, training, and riding practices utilized [2,11]. The core domains identified in this study could provide a viable starting point to develop this.…”
Section: Essential Versus Important: Evidence-informed or Opinion-based?mentioning
confidence: 99%
See 4 more Smart Citations
“…A good starting point to promote sporthorse health and welfare and establish an effective SLO for horse sports would be to develop an evidence-based infrastructure to inform the management, training, and riding practices utilized [2,11]. The core domains identified in this study could provide a viable starting point to develop this.…”
Section: Essential Versus Important: Evidence-informed or Opinion-based?mentioning
confidence: 99%
“…The FEI's EEWC outline their vision for the future across their 24 recommendations: A 'Good life for horses' advocating an ethical and evidence-based approach that establishes a trusted and proactive culture of accountability, responsibility, and transparency across equestrian sport [70]. Increased research and education are key enablers identified to support this vision to inform practice and regulation across the sector, underpin decision-making to promote a good life for horses, enable accurate welfare assessment, and support policy makers and regulatory bodies to act as an advocate for the horse across competitive horse sports [2,3,55]. A good starting point, suggested by Douglas et al [3], is for individuals to embrace their collective responsibility by asking "Should I?"…”
Section: Prioritizing Performance and Welfarementioning
confidence: 99%
See 3 more Smart Citations